ANALISIS USER EXPERIENCE DAN INNOVATION RESISTANCE PENGGUNAAN APLIKASI MYPERTAMINA MENGGUNAKAN PENDEKATAN UTAUT2 DAN UCD - Hairadifa, Rifka Putri; Asra, Taufik; Sinnun, Ahmad (INTI Nusa Mandiri, 2025)
Pertamina Company launched the MyPertamian Application as a solution to the problem of uneven distribution of subsidized fuel and the implementation of non-cash payment innovations during the pandemic.  However, the mismatch between the implementation of the innovation and the habits of the community has led to a rejection of the use of the application.  Therefore, with this research, it is expected to identify the factors influencing the rejection of innovation usage using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) approach, with SmartPLS measurement and System Usability Scale (SUS) measurement as the readiness for application usage among 48 respondents through questionnaire completion.  The research results show that aspects such as ease of use, usefulness, and perceived value of the MyPertamina application significantly influence user acceptance and the decision to adopt the application.  On the other hand, innovation resistance appears in the form of user concerns about change, complexity, and data security.  Therefore, design implications and development strategies can be identified to enhance user experience and reduce innovation barriers.